Security and Privacy in Communication Networks 8th International ICST Conference, SecureComm 2012, Padua, Italy, September 3-5, 2012. Revised Selected Papers - Keromytis, Angelos D.; Pietro, Roberto Di.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume presents the refereed proceedings of the 8th International ICST Conference on Security and Privacy in Communication Networks, SecureComm 2012, held in Padua, Italy, in September 2012. The 21 revised papers included in the volume were carefully reviewed and selected from 73 submissions. Topics covered include crypto and electronic money; wireless security; web security; intrusion detection and monitoring; and anonymity and privacy.
Crypto and electronic money -- Wireless security -- Web security -- Intrusion detection and monitoring -- Anonymity and privacy.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Computers and civilization; Management information systems; Computer Science; Systems and Data Security; Management of Computing and Information Systems; Computers and Society; Computer Communication Networks; Data Encryption; Information Systems Applications (incl. Internet).; Electronic books